The Early Retirement Age Increment in Case of Republic of Srpska Pension Fund - Bošnjak, Nikolina; Zvjezdana Bošnjak, (European Journal of Multidisciplinary Studies, 2016)
The worldwide trends of increased life expectancy and decreasing fertility are considered to be the main driving forces of pension funds sustainability crisis. Different countries are facing its pension fund’s financing problems on different ways, but in general there is evident trend of retirement age rising, especially among developed countries. The Republic of Srpska is currently having one of the lowest pensionable age limits in Europe. At the same time its pension fund is for years operating with significant negative financial result. In this paper we will estimate and analyse the effects of retirement age limit rising in Republic of Srpska in order to observe will the rising of early retirement age on 62 years old bring only short-term or long-term results.
Keywords: Pension sustainability, Retirement age, Parametric reforms effects